Efficacy of catheter‐based drug delivery in a hybrid in vitro model of cardiac microvascular obstruction with porcine microthrombi - Yannick Rösch; Thorald Stolte; Miriam Weisskopf; Sabrina Frey; Rob Schwartz; Nikola Cesarovic; Dominik Obrist (Wiley, 2024)
Abstract Microvascular obstruction (MVO) often occurs in ST‐elevation myocardial infarction (STEMI) patients after percutaneous coronary intervention (PCI). Diagnosis and treatment of MVO lack appropriate and established procedures. This study focused on two major points by using an in vitro multiscale flow model, which comprised an aortic root model with physiological blood flow and a microfluidic model of the microcirculation with vessel diameters down to 50 μm. First, the influence of porcine microthrombi (MT), injected into the fluidic microchip, on perfusion was investigated. We found that only 43% of all injected MT were fully occlusive. Second, it could also be shown that the maximal concentration of a dye (representing therapeutic agent) during intracoronary infusion could be increased on average by 58%, when proximally occluding the coronary artery by a balloon during drug infusion. The obtained results and insights enhance the understanding of perfusion in MVO‐affected microcirculation and could lead to improved treatment methods for MVO patients.